Foodgrain production and imports: toward self-sufficiency in rice? - Dorosh, Paul A. (International Food Policy Research Institute, 2000)
Bangladesh faces huge obstacles in its efforts to increase foodgrain production, raise rural incomes, and reduce food insecurity. In this country of nearly 125 million people living in an area of approximately 143,000 square kilometers, there is immense population pressure on the available cultivable land. Average farm size is only 0.8 hectare, and there is virtually no scope for expansion of cultivated land (although some expansion in multiple cropping is possible). Moreover, agricultural production is susceptible to the vagaries of the weather: floods, droughts, and cyclones frequently cause substantial damage.